Asymmetry of brain and behavior in animals: Its development, function, and human relevance. Issue 6 (22nd January 2014) - Rogers, Lesley J.
Abstract : Summary: Since the discovery of brain asymmetry in a wide range of vertebrate species, it has become possible to study development and expression of lateralized behavior accurately in well‐controlled experiments. Several species have emerged as useful models for investigating aspects of lateralization. Discussed here are: (1) the influence of exposure to light during embryonic development on lateralization, (2) effects of steroid hormones on lateralization, (3) developmental changes in which hemisphere is controlling behavior, and (4) asymmetry in memory formation and recall. The findings have bearing on understanding the development of hemispheric specialization in humans and are likely to provide insight into dysfunctional behavior associated with weak or absent lateralization and impaired interhemispheric communication (e.g., autism, schizophrenia, and dyslexia). This review features research on chicks, pigeons, and zebrafish, with the addition of some recent evidence of lateralization in bees. Discoveries made using these species have highlighted the interaction between experience, hormones, and genetic factors during development, and have provided some of the first clear evidence of the advantage of having a lateralized brain. genesis 52:555–571, 2014. © 2014 Wiley Periodicals, Inc.